Contemporary Facets in Human Resource Management - Dimitrov, Kiril (Research Papers, 2009)
This study analyses the contemporary comprehension of human resource management – essence, scope, position, role and importance, by considering different nuances, shaped under the influence of the current economic conditions. This is achieved by identification of factors, defining the meaning of human resource management, including its strategic direction, and well-grounded development of a useful definition of human resource management in Bulgarian context, as the events in this sphere from the last twenty years are classified into three sub-periods.